2004
DOI: 10.1002/rcm.1470
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carnitine and acylcarnitines in plasma by high‐performance liquid chromatography/electrospray ionization ion trap tandem mass spectrometry

Abstract: A high-performance liquid chromatography/mass spectrometry method was developed for the determination of carnitine, its biosynthetic precursor butyrobetaine, and eight acylcarnitines in plasma. The procedure includes a solid-phase extraction for carnitine and short- and medium-chain acylcarnitines, and a liquid-liquid extraction for protein-bound long-chain acylcarnitines, followed by separation on a reversed-phase column in the presence of a volatile ion-pairing reagent. Detection was achieved using an ion-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 26 publications
(28 reference statements)
3
61
0
Order By: Relevance
“…Plasma concentrations of IL-6 and TNF-α were measured using Quantine High Sensitivity kits (R&D Systems) and total adiponectin concentrations were measured using a double-antibody RIA kit (Linco). Plasma concentrations of acylcarnitines were measured by LC-MS/ MS, as previously described (47). Plasma amino acid concentrations were measured as the trifluoro-acetamide n-butyl ester derivatives (1), using GC-MS (HP 5973MSD; Hewlett-Packard).…”
Section: Mri Measurements Of Visceral and Subcutaneous Fat Volumesmentioning
confidence: 99%
“…Plasma concentrations of IL-6 and TNF-α were measured using Quantine High Sensitivity kits (R&D Systems) and total adiponectin concentrations were measured using a double-antibody RIA kit (Linco). Plasma concentrations of acylcarnitines were measured by LC-MS/ MS, as previously described (47). Plasma amino acid concentrations were measured as the trifluoro-acetamide n-butyl ester derivatives (1), using GC-MS (HP 5973MSD; Hewlett-Packard).…”
Section: Mri Measurements Of Visceral and Subcutaneous Fat Volumesmentioning
confidence: 99%
“…In a subsequent purifi cation step, cation exchange solid-phase extraction using silica gel was applied; this has previously been shown to be effective to suffi ciently isolate acylcarnitines from urine and plasma (29)(30)(31)(32). The relatively apolar ratio of 6.5 parts acetonitrile-methanol (4:1, v/v) to 1 part sample volume resulted in suffi cient retention (96.0% to 99.5%) of acylcarnitines to the silica-gel columns.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized, controlled studies and a meta-analysis suggested that L-carnitine supplementation might have a positive effect on response to EPO in longterm hemodialysis patients (17)(18)(19)(20)(21). Each of these studies included around 30 patients or fewer, highly selected for probable rHuEPO resistance secondary to carnitine deficiency, defined by a free carnitine level ,30 mmol/L (or total ,40 mmol/L) (22). These results led to the recommendation of L-carnitine treatment in hemodialysis patients for symptoms potentially related to carnitine deficiency, such as hyporesponsive rHuEPO-dependent anemia (23).…”
Section: Introductionmentioning
confidence: 99%